Children’s rights to education in South Africa twenty years after democracy: a reflection on achievements, problems and areas for future action - Chitsamatanga, B.B.; Rembe, N.S. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Education is the most powerful weapon that can be used to change the world. These noble words by Nelson Mandela provide a yardstick against which South Africa can measure whether the rights of the child, key of which is the right to education, are progressively being realised. Towards this end, education is seen as the ultimate foundation and solution for the attainment of freedom, democracy and human rights; social justice and equality for South African children. Thus, the question remains: after more than twenty years of democracy, to what extent can South Africa pride herself of having achieved this noble goal? This article reflects on the national effort to realise the rights of children to education against the frameworks provided for in international and regional instruments. The latter require governments’ commitment to ensure that the rights of children to education in particular, are implemented and respected. An analysis will be made on how the new democratic government has succeeded to reverse the discriminatory policies, law and practice of the apartheid era. It further discusses how the existing education system translates the attainment of children rights to education in terms of the standard and quality of teaching and learning; existing school facilities; racial segregation; human and financial resources; and safe school learning environment. The article concludes by identifying measures that need to be taken by all stakeholders in order to promote the realisation of children’s right to education.